2019
DOI: 10.7717/peerj.6945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music interventions on anxiety during labor: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Anxiety is commonly experienced during the delivery process and has shown to have adverse effects on maternal and infant health outcomes. Music interventions tend to reduce the effects of anxiety in diverse populations, are low cost, are easily accessible, and have high acceptability. The aim of this review and meta-analysis was to assess the effectiveness of music interventions in reducing anxiety levels among women during labor. Methods Seven databases from inception to the end of December, 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 42 publications
2
23
2
1
Order By: Relevance
“…In the current review, we conducted a more comprehensive research of seven databases and pooled eight RCTs to provide updated evidence that listening to music during pregnancy may have a beneficial effect. These results conform to the findings of a prior review regarding the use of music to reduce anxiety in pregnant women undergoing cesarean section or labor process [34].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current review, we conducted a more comprehensive research of seven databases and pooled eight RCTs to provide updated evidence that listening to music during pregnancy may have a beneficial effect. These results conform to the findings of a prior review regarding the use of music to reduce anxiety in pregnant women undergoing cesarean section or labor process [34].…”
Section: Discussionsupporting
confidence: 89%
“…This considerable variation may lead to more heterogeneous results regarding psychological or physiological outcomes [12,13]. However, a previous meta-analysis revealed a significant difference in pregnant women using self-chosen music during labor [34]. Furthermore, a Cochrane review demonstrated that participant-preferred music had greater anxiety-reducing effect than researcher-selected music in patients with chronic heart disease [11].…”
Section: Discussionmentioning
confidence: 99%
“…This updated review is consistent with previous systematic reviews related to the effects of musical intervention on lowering anxiety and pain intensity in study participants during labor [3.10.19]. Additionally, this metaanalysis found a significant decrease in the vital signs of heart rate, SBP and DBP after musical intervention, which is consistent with Lin et al [10]. Musical intervention reduces the objective parameters of HR and BP, which supports the positive findings of the effects of musical intervention on the subjective parameters of stress and anxiety [49].…”
Section: Similarities or Differences With Other Studies Or Reviewssupporting
confidence: 90%
“…Increased levels of stress and anxiety can lead to negative effects on both maternal and child outcomes [4]: Antenatal anxiety and depression can result in increased maternal preterm birth rates and low birth weight [5][6][7]. High levels of anxiety in women during labour and in women undergoing Caesarean section (CS) may result in higher infection risk, elevated blood pressure and heart rates, increased cortisol levels and slower wound healing [8][9][10]. Moreover, high levels of anxiety can also lead to increased analgesic consumption in women undergoing CS, who may also experience higher levels of post-Caesarean pain [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation